Development of an enhanced student identification system - Oyedejı, Ajibola; Okakwu, Ignatius; Abolade, Olatilewa (Fırat Üniversitesi, 2023)
Identification, verification, and student authentication to prevent impersonation during examinations are essential. This is a predominant issue in institutions in developing countries such as Nigeria. This paper designed and developed an enhanced student identification and authentication system capable of verifying and admitting only duly registered students into an examination hall in Nigerian higher educational institutions. The system uses radio frequency identification and biometrics for identification and comprises an Arduino microcontroller, a fingerprint reader, radio frequency identification (RFID) reader with a user-friendly desktop application. The registered students' data and fingerprints are captured and stored in the database. The verification and authentication of the student's identity are observed when the stored information matches the identity of the student presenting the RFID card or fingerprint. The enhanced identification system was rated as good with an average of 4.35 out of 5.0 based on the functionality, ease of use, efficiency and user interface. The developed system is more reliable and efficient than the existing systems in Nigerian institutions as it provides solutions for the identification and verification of students accurately.
Keywords: Bioengineering (Other); Biyomühendislik (Diğer)